Japanese culture and behavior - Lebra, Takie Sugiyama (University Press of Hawaii, 1974)
Addressing both the cultural context of behavior and the behavioral manifestations of culture, the 1974 edition of this text yielded a multifaceted yet remarkably integrated portrait of the Japanese. Within its pages classical stereotypes and seemingly contradictory behaviors were appraised, put into perspective, and made comprehensible.